1998
DOI: 10.1021/ef970148c
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Dispersed Molybdenum Catalyst and Mechanistic Studies for Upgrading Extra-Heavy Crude Oil Using Methane as Source of Hydrogen

Abstract: A dispersed molybdenum catalyst, derived from MoO 2 (acac) 2 (where acac ) acetylacetonate), was used for upgrading extra-heavy crude oil in the presence of methane as source of hydrogen. The experiments were carried out in a batch reactor at a final CH 4 pressure of 11 MPa, 410 °C, for 1 h. An increase of 7°in the API gravity, 16% of reduction in sulfur content, and 55% conversion of the >500 °C fraction with respect to the original crude was found. The catalyst was analyzed by XPS and EDAX from the coke isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…Also, similar results were obtained previously for extra-heavy crude oil upgrading under higher temperature (380-420 °C) thermal [24] and catalytic conditions (Mo-containing catalyst) [22]. The incorporation of methyl groups, coming from methane, into the crude oil molecules was confirmed by isotopic carbon distribution measurements ( 13 C/ 12 C) using 13 CH4 as a source of hydrogen [22]. However, the addition of methane during the upgrading reaction is very small estimated value (0.01% w/w) and alternative explanations can be suggested as well.…”
Section: Mechanistic Considerationssupporting
confidence: 88%
See 3 more Smart Citations
“…Also, similar results were obtained previously for extra-heavy crude oil upgrading under higher temperature (380-420 °C) thermal [24] and catalytic conditions (Mo-containing catalyst) [22]. The incorporation of methyl groups, coming from methane, into the crude oil molecules was confirmed by isotopic carbon distribution measurements ( 13 C/ 12 C) using 13 CH4 as a source of hydrogen [22]. However, the addition of methane during the upgrading reaction is very small estimated value (0.01% w/w) and alternative explanations can be suggested as well.…”
Section: Mechanistic Considerationssupporting
confidence: 88%
“…(1) Egiebor and Gray found methyl-and dimethyl-substituted products by GC analysis of the donor solvent (tetralin), which was attributed to direct alkylation by reaction with methane during iron catalyzed coal liquefaction [23]. Also, similar results were obtained previously for extra-heavy crude oil upgrading under higher temperature (380-420 °C) thermal [24] and catalytic conditions (Mo-containing catalyst) [22]. The incorporation of methyl groups, coming from methane, into the crude oil molecules was confirmed by isotopic carbon distribution measurements ( 13 C/ 12 C) using 13 CH4 as a source of hydrogen [22].…”
Section: Mechanistic Considerationssupporting
confidence: 71%
See 2 more Smart Citations
“…Moreover, ultradispersed catalysis was successfully applied for upgrading of extra heavy oil. Ovalles et al [5] reported a 7°increase in the API gravity, 55% conversion of the heavy fraction and a 16% reduction in the sulfur content using ultradispersed molybdenum catalyst. During heavy oil recovery and upgrading, the sulfur content of heavy oil declines as a result of aqua-thermolysis [6] and hydrodesulfurization [5] reactions, which lead to the evolution of hydrogen sulfide, H 2 S (g) , throughout the oil phase.…”
Section: Introductionmentioning
confidence: 99%